Host ecology shapes chigger mite parasitism on wild, captive, and domestic birds across Malaysia and Thailand - Praveena, Rajasegaran; Sirikamon, Koosakulnirand; Krairat, Eiamampai; Jirut, Khamaye; Ahmad Khusaini, Mohd Kharip Shah; Nuramirah Diyanah, Mohd-Johan; Siti Nurul Izzah, Mohd-Azami; Muhammad Al Amin, Mohd-Redzuan; Mohamad Fizl Sidq, Ramji; Mohammad Saiful, Mansor; Philip, Round; Sazaly, Abu Bakar; et al. (Elsevier B.V., 2026)
Southeast Asia is one of the global biodiversity hotspots, renowned for its rich bird fauna and diverse arthropod communities among other taxa. This comprehensive multisite study investigated trombiculid mite (chigger) infesta tion patterns among birds in Thailand and Malaysia, focusing on the interactions between host taxonomy, host ecological traits, and environmental factors. Previous surveys have frequently recorded Leptotrombidium spp., the main vectors of scrub typhus in humans, parasitising birds. We examined 2006 birds representing 191 species across 51 families and 13 orders, revealing a parasitism rate of 17.74% (356 infested birds). Twenty-one chigger species were identified across diverse host habitat types, including captivity, urban and rural settlements, agricultural lands, aquatic environments, and diverse forest ecosystems. The most prevalent species were Toritrombicula densipiliata (4.3% of individual birds infested), followed by Odontacarus audyi (3.9%) and Eutrombicula wichmanni (3.6%, only recorded from Thailand), whereas Leptotrombidium spp. were rare (0.3% in aggregate). Host ecology, including habitat breadth, geographical scale, and degree of forest dependency, significantly impacted infestation patterns. Notably, bird species with no forest dependency (e.g., synanthropic species in urban environments) exhibited the lowest infestation rates and chigger species richness. Analysis by season was restricted to Malaysia, where birds captured during the drier period showed higher chigger diversity compared to the wet season. There was no host phylogenetic signal associated with chigger infestation or species richness. However, in a meta-analysis restricted to five heavily-sampled bird species, the significant effects of host ecology were confirmed. This study provides critical insights into bird-parasite associations, offering valuable information for the ecological monitoring of ectoparasite infestation and potential disease vectors. The results have important implications for understanding public health risks, wildlife conservation, and the complex disease ecology of understudied ectoparasitic relationships in tropical ecosystems.